A case report: multiple right ventricular diverticula with constrictive pericarditis and right heart failure. Issue 2 (24th May 2019) - Iqbal, Sohail; Abidin, Nik; Irwin, Richard Bruce; Schmitt, Matthias
Abstract: Background: Right ventricular diverticula (RVD) are very rare congenital anomalies and their association with constrictive pericarditis is even rarer. So far, only one case has been published in literature. Case summary: We report a case of multiple congenital RVD with constrictive pericarditis and right heart failure which was incidentally identified on surveillance computed tomography (CT) for abdominal lymphangioma. Interval CT, echocardiography, and cardiac magnetic resonance imaging (CMR) studies were performed and reviewed. Computed tomography abdomen showed hepatic congestion with features of portal hypertension, increasing size of the RVD on review of serial CTs, and eccentric foci of pericardial calcification. Echocardiography performed for breathlessness demonstrated supranormal early diastolic tissue velocities with average of 19.8 cms −1 and a septal bounce phenomenon on m-mode imaging suggesting constrictive physiology, which triggered a CMR referral. Cardiac magnetic resonance imaging HASTE and right ventricular (RV) outflow tract imaging showed four outpouchings along RV free wall, the largest measuring 4.5 × 2 cm with a sizeable neck. These outpouchings displayed a trabecular network and/or were contractile aiding the diagnosis of diverticula as opposed to aneurysms. Right ventricular function was moderately compromised, whereas left ventricular function was preserved. Discussion: Right ventricular diverticula can be associated with, and potentially be causative of, pericardial thickening and calcification eventually leading to constrictive pericarditis and heart failure.